FACTORS OF INFLUENCE IN CHOOSING ACCOMMODATION: A STUDY WITH REFERENCE TO MAS VILLAGE, AN ARTISTIC HERITAGE VILLAGE IN UBUD - BALI - Pertiwi, Putu Ratih; Sulistyawati, Agung Sri (Institut Pariwisata dan Bisnis Internasional, 2020)
This paper attempts to identify the factors that influence foreign tourists to choose accommodations in Mas Village – an artistic heritage village in Ubud, Bali. As the accommodations are in the village, tourists’ motive in choosing accommodation may be different from accommodations in the big cities. The research took place in Mas Village, considering this village has been experiencing a big spike in the growth of tourists accommodation, while based on the data of 2012 until 2017 – the 87 percents of the tourists who visit this village are foreign tourists. It is known that Mas Village is one of villages in Bali fundamentally identified as an artistic countryside by focusing in artistic of wood carving since 1930s. Primary data is collected from the foreign tourists as respondents who stay in accommodations in Mas Village during June 2019, then the data is analysed using Factor analysis. The result of the factor analysis shows that location emerges as the key factor that influences tourists in choosing accommodation among three others factors. Additionally, an interesting finding from the study is how local touch and security form as one factor. By understanding the influence factors, those accommodations in Mas Village will be able to develop marketing strategies that appeal to this segment of tourists and create meaningful points of differences. However, as this research is focusing in foreign tourists, the future studies concerning how domestic tourists choose their accommodation in Mas Village is highly expected, in order to compare with foreign tourists’ perspective in this research.